Potensi Budaya Menjadi Unggulan Desa Wisata Di Kepulauan Karimunjawa, Kabupaten Jepara: Penelitian Tentang Potensi Ragam Budaya Lokal Bagi Daya Tarik Pariwisata - Rahmad Purwanto Widiyastomo; Christine Diah W; Endang Swastuti (Public Service and Governance Journal, 2024)
The aim of this research is to describe the potential of various traditions and culture of the community as superior tourism in addition to natural potential, coastal tourism and small islands in the Karimunjawa Islands which are administratively in the Karimunjawa sub-district. The diversity of cultural arts, house buildings and philosophies, traditional customs, marriage and traditional technology in society is a potential for excellence, cultural wealth both in the form of objects and intangible culture (folklore, mythology, stories, pencak silat, sound arts and religious rites, especially religion Islam). Likewise, the development of the creative economy (local culinary, processed staple foods and others). This superior potential is a complement to the development of village tourism in Karimunjawa for both domestic and foreign tourists.